Weight-band dosing tables: Simplifying paediatric ART - James J C Nuttall (AOSIS, 2009)
One of the obstacles to scaling up paediatric antiretroviral therapy (ART) coverage in resource-limited settings (RLS) is the relative complexity of paediatric dosing. There is a need to simplify ART in order to facilitate treatment initiation and ongoing management of infants and children by healthcare providers, as well as to support adherence within the home. This article reviews the development of weight band dosing tables as a simplification strategy for the delivery of paediatric ART.